Fuzzy logic traction control system for a golf cart - Rahman, Mohammed Ataur; Hossain, Altab (2011)
This study presents on the development of an intelligent traction control system (ITCS) to optimize the power consumption with precisely maintain the traction of the vehicle in different terrain conditions. Compared with conventional control approach, fuzzy logic approach is more efficient for nonlinear dynamic systems and embedding existing structured human knowledge into workable mathematics. This study also investigates the relationship between vehicle’s input parameters of power supply (PI) and moisture content (MC) and output parameter of traction force (TF). Experiment has been conducted in the field to investigate the vehicle traction and the result has been compared with the developed fuzzy logic system (FLS) based on Mamdani approach. Results show that the mean relative error of actual and predicted values from the FLS model on TF is found as 7.68 %, which is less than the acceptable limit of 10%. The goodness of fit of the prediction value from FLS is found close to 1.0 as expected and hence shows the good performance of the developed system.